Preparation and Characterization of Copper Imprinted PVA/Alginate Based Beads for Removal of Dyes from Aqueous Solution - Bingong, Ishaku Hamidu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Cu(II)-imprinted polymeric beads were formed using PVA/SA and adsorption studies were carried out to check the effectiveness of the beads on dye and copper sorption. The adsorption studies were carried out by investigating the point zero charge of the beads which was at 3.04, effect of pH was investigated for methylene blue dye which pH 8 gave the best removal efficiency of about 98% and for copper, pH 5 gave the best removal efficiency, effect of dosage which an increase in dosage resulted to decreased removal efficiency so 0.1 g/L of the beads were used throughout for both adsorbates in this study, effect of initial concentration where removal efficiency increased with increase in initial adsorbate concentration, effect of time in which equilibrium was reached after 360 minutes for methylene blue dye sorption, effect of temperature which revealed that at higher temperatures, methylene blue dye removal efficiency decreased which implies that the adsorption process was exothermic while for copper, it showed it was endothermic. Adsorption kinetic studies were also carried out and it followed a pseudo-second order kinetics while isotherm studies revealed that the study is best described by the Freundlich isotherm which predicts heterogenous adsorption mechanism. From thermodynamic studies, it was deduced from ΔG o and ΔH o values that the process is spontaneous and exothermic for MB and spontaneous but endothermic for copper. Keywords: Cu(II)-imprinted polymeric beads; Adsorption studies; Methylene blue dye; Copper; Adsorption kinetics; Isotherm studies.

ÖZ: PVA/SA kullanılarak Cu(II) izlenimli polimerik boncuklar oluşturuldu ve boncukların boya ve bakır emilimi üzerindeki etkinliğini kontrol etmek için adsorpsiyon çalışmaları yapıldı. Adsorpsiyon çalışmaları boncukların sıfır noktası yüküne pH 3.04 değerinde ulaşıldığını gösterdi. Metilen mavisi boyası için yapılan pH etkisi çalışması pH 8 değerinde 98% ile en iyi boya giderim verimliliğini gösterirken bakır için bu değer pH 5 olarak bulunmuştur. Dozajdaki artışın giderim etkinliğinin azalmasına yol açtığı ölçüldü ve bu nedenle her iki adsorbat için de boncuklar 0.1 g/L olacak miktarda kullanılmıştır. Giderim etkinliğinin adsorbat maddenin başlangıç konsantrasyonuna olan bağlılığının ölçüldüğü çalışmada giderim etkinliğinin başlangıç konsantrasyonundaki artışa bağlı olarak arttığını göstermiştir. Metilen mavisi boyası için yapılan süre etkisi çalışması 360 dakika sonra dengeye ulaşıldığını göstermiştir. Sıcaklığın giderim etkinliği üzerine olan etkisi ölçüldü ve yüksek sıcaklıklarda metilen mavisi boyasının gideriminin azaldığı görülüp metilen mavisi boyasının giderim işleminin ekzotermik olduğunu gösterirken bakır için ise bu işlemin endotermik olduğu görüldü. Adsorpsiyon kinetik çalışmaları da yapıldı ve sahte ikinci derece kinetiğe uyduğu hesaplandı, izoterm çalışmaları ise çalışmanın en iyi heterojen adsorpsiyon mekanizmasını öngören Freundlich izotermi tarafından tanımlandığını ortaya koydu. Termodinamik çalışmalardan elde edilen ΔG o ve ΔH o değerlerinin hesaplanması ve yorumlanması sonucu metilen mavisi boyasının gideriminin spontan ve ekzotermik ve bakır için spontan fakat endotermik olduğu çıkarılmıştır. Anahtar kelimeler: Cu(II) izlenimli polimerik boncuklar; Adsorpsiyon çalışmaları; Metilen mavisi boyası; Bakır; Adsorpsiyon kinetiği; Izoterm çalışmaları.
Master of Science in Chemistry. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2020. Supervisor: Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Polymers; Cu(II)-imprinted polymeric beads; Adsorption studies; Methylene blue dye; Copper; Adsorption kinetics; Isotherm studies